Crystallization and preliminary X‐ray analysis of a UDP‐MurNAc‐tripeptide D‐alanyl‐D‐alanine‐adding enzyme (PaMurF) from Pseudomonas aeruginosa. Issue 5 (22nd May 2013) - Majce, Vita; Ruane, Karen M.; Gobec, Stanislav; Roper, David I.
<x xml:space="preserve">Abstract</x> The ATP‐dependent UDP‐MurNAc‐tripeptide:D‐Ala‐D‐Ala ligase MurF catalyses the last step in the cytoplasmic phase of peptidoglycan biosynthesis, which is critical in the formation of the bacterial cell wall and in the recycling of peptidoglycan intermediates. In this study, the crystallization of MurF from the Gram‐negative pathogen Pseudomonas aeruginosa in the presence of its UDP‐MurNAc‐tripeptide substrate is reported. The crystals belonged to space group P212121, with unit‐cell parameters a = 57.81, b = 87.29, c = 92.61 Å, and data were collected to 1.92 Å resolution, allowing study of the enzyme in the substrate‐liganded form for the first time.